Pengembangan KIT Meriam Telur untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Abdul Wahab (Jurnal Didaktika Pendidikan Dasar, 2021)
This study aims to create a practical tool for hydrostatic pressure material, increasing student motivation, and learning outcomes. The lack of student motivation, namely the desire to learn science subjects and the learning outcomes of hydrostatic pressure material is caused by several factors, one of which is the lack of teaching aids or practical tools for hydrostatic pressure material. The study was conducted using a one-group pre-test – post-test trial design, while the development of the Egg Cannon Kit used the ASSURE model which consisted of 6 stages, namely Analyzer learner characteristic, (2) State standard and performance objective, (3) Select methods, Media, and materials, (4) Utilize technology, media, and materials, (5) Require learner participation and (6) Evaluation and revision. The research on the development of the Egg Cannon Kit was tested on 8E grade students consisting of 32 students with heterogeneous compositions. The use of the Egg Cannon Kit in learning can increase students' learning motivation in this case the student's desire to learn about science subjects, especially hydrostatic pressure material by 43.36% and increase learning outcomes with an average n-gain of 0.8 in the high category.